Mental health among transgender women living with HIV in Canada: findings from a national community-based research study. Issue 2 (1st February 2021) - Lacombe-Duncan, Ashley; Warren, Laura; Kay, Emma Sophia; Persad, Yasmeen; Soor, Jaspreet; Kia, Hannah; Underhill, Angela; Logie, Carmen H.; Kazemi, Mina; Kaida, Angela; de Pokomandy, Alexandra; Loutfy, Mona
ABSTRACT: Antiretroviral therapy adherence among transgender (trans) women living with HIV (WLWH) is negatively impacted by depression and post-traumatic stress disorder (PTSD). Yet, little is known about factors associated with depression or PTSD among trans WLWH. Using cross-sectional data from a national community-based study of 1422 WLWH ( n = 53 trans women), we characterized the prevalence of depressive and PTSD symptoms among trans WLWH and examined associations between factors (e.g., Trans stigma) and depressive and PTSD symptoms. Nearly half of participants reported clinically significant PTSD (45.3%) and depressive symptoms (45.3%) [mean Post-traumatic Stress Disorder Civilian Checklist Version-C score 13.8 (SD = 5.8); mean Center for Epidemiological Studies – Depression score 9.4 (SD = 8.0)]. Univariate linear regression analyses showed that <95% adherence, higher internalized HIV-related stigma, frequency of past-month hazardous alcohol use, and current injection drug use were significantly associated with both higher PTSD and depressive symptom scores, and higher resilience and social support with lower scores. A history of violence in adulthood was associated with higher depressive symptoms scores, whereas sexual relationship power and less difficulty meeting housing costs were associated with lower scores. Findings suggest a need for multi-level interventions to reduce barriers to mental wellbeing while fostering resilience and social support.